2018
DOI: 10.1142/s1084946718500255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Informal Sector Competition on Firm Performance: Some Lessons From South-East Europe

Abstract: A widespread assumption is that competition from the informal sector has a negative impact on the firm performance of legitimate enterprises. This is because of the unfair competition they face from such enterprises in the informal sector. The aim of this paper is to provide an evidence-based evaluation of whether this is the case based on an analysis of the relationship between the firm performance of enterprises and their perception of the prevalence of informal sector competition. To do so, data is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…On the one hand, it advances understanding of whether formal sector enterprises that have to compete against unregistered or informal sector business ventures suffer deleterious effects. Until now, the evidence on this issue has been confined to the countries of the developing world (Williams andKedir, 2016, 2017;Williams et al, 2017) and some transition economies (Williams and Bezeredi, 2018). This study reveals that in the developed world, namely Italy, formal sector enterprises that have to compete against unregistered or informal sector business ventures suffer deleterious effects in terms of annual sales growth and annual productivity growth rates, albeit not employment growth rates.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the one hand, it advances understanding of whether formal sector enterprises that have to compete against unregistered or informal sector business ventures suffer deleterious effects. Until now, the evidence on this issue has been confined to the countries of the developing world (Williams andKedir, 2016, 2017;Williams et al, 2017) and some transition economies (Williams and Bezeredi, 2018). This study reveals that in the developed world, namely Italy, formal sector enterprises that have to compete against unregistered or informal sector business ventures suffer deleterious effects in terms of annual sales growth and annual productivity growth rates, albeit not employment growth rates.…”
Section: Discussionmentioning
confidence: 87%
“…Three studies have so far shown this to be the case in the developing world, namely in India (Williams and Kedir, 2016), Africa (Williams and Kedir, 2017) and across 142 countries in the developing world (Williams et al, 2017). Meanwhile, one study has examined this issue in transition economies, namely a study of 1,430 enterprises in Bulgaria, Croatia and FYR Macedonia (Williams and Bezeredi, 2018). The finding is that enterprises asserting that their competitors participate in the informal sector have significantly lower real annual sales growth rates compared with those who assert that their competitors do not participate in the informal sector.…”
Section: Effects Of Unregistered and Informal Sector Enterprise: A Literature Reviewmentioning
confidence: 99%
“…Studies evaluating the varying level informal sector competition across countries have so far been confined to a study of 142 countries, which again reveals the same finding that modernization, political economy and institutional theories apply but not neoliberal theory (Williams and Kedir, 2018a) and a study of three South-Eastern European countries, which shows that informal sector competition leads to poorer firm performance (Williams and Bezeredi, 2018b). To further advance understanding of the prevalence of informal sector competition, this paper focuses on Latin America and the Caribbean countries to evaluate which, if any, of these theories are valid in this global region.…”
Section: Theorizations Of the Variable Commonality Of Informal Sectormentioning
confidence: 94%
“…In emerging market economies, the formal private sector must overcome the challenges that result from weak institutional environments but also from the unfair competition the informal sector poses as this sector is largely unregulated and is not usually subject to taxes or other administrative burdens (Bloom and Van Reenen, 2010;Williams and Bezeredi, 2018). So stiff market competition, including from the informal sector, is expected to incentivise firms to seek and learn new management practices so as to cement or expand their market share.…”
Section: Firm Characteristicsmentioning
confidence: 99%